Substance use and incidence of metabolic syndrome before midlife among military adults: the CHIEF cohort study - Liu, Wei-Nung; Hsu, Yi-Chiung; Lin, Yen-Po; Tsai, Kun-Zhe; Chang, Yun-Chen; Liu, Pang-Yen; Lin, Gen-Min (Frontiers in Public Health, 2024)
Backgrounds Habitual substance use, i. e., alcohol, tobacco and betel nut, has been found with an increased risk of metabolic syndrome (MetS) in the general population, whereas the association remains unclear in physically fit military personnel. This study aimed to investigate the combination of these substances use and their associations with new-onset MetS in the military. Methods A total of 2,890 military men and women, aged 18–39 years, without MetS were obtained from the cardiorespiratory fitness and health in eastern armed forces study (CHIEF) in Taiwan and followed for incident MetS from baseline (2014) through the end of 2020. Incident MetS event was defined by the International Diabetes Federation guideline and confirmed in the annual health examinations. A self-report was used to assess the alcohol, tobacco and betel nut use status (active vs. former/never). Multivariable Cox regression model was performed to determine the association with adjustments for sex, age, body mass index and physical activity at baseline. Results At baseline, there were 279 active betel nut chewers (9.7%), 991 active smokers (34.3%) and 1,159 active alcohol consumers (40.1%). During a mean follow-up of 6.0 years, 673 incident MetS (23.3%) were observed. As compared to no substance users, only one substance, and two and three substances users had a greater risk of incident MetS [hazard ratios (HRs) and 95% confidence intervals: 1.27 (1.06–1.54), 1.38 (1.12–1.69) and 1.78 (1.37–2.32), respectively]. In subgroup analyses, the risk of incident MetS in two and three substances users was significantly greater in those free of baseline low high-density lipoprotein [HRs: 1.54 (1.21–1.95) and 2.57 (1.92–3.46), respectively], as compared to their counterparts (both p for interactions <0.05). Conclusion A dose-response association of more substances use for new-onset MetS was noted in military personnel. This finding suggests that the combined alcohol, tobacco and betel nut use may play a role in the development of MetS. Further study is required to establish causation and to investigate the potential benefits of substance use cessation in reducing the risk of MetS.